USULAN PERAWATAN MESIN SECARA PREVENTIF DENGAN PENDEKATAN MODULARISASI DESAIN PADA PT. BAI - Amal Witonohadi; Tiena Gustina Amran; Niken Herawati (JURNAL TEKNIK INDUSTRI, 2013)
PT. BAI produce polymer filter system components, such as the spin pack, candle filters, leafdiscs, gaskets and so forth. Problems that occur in the form of decreased reliability of machinedowntime resulting in large engine stalled, causing the production process, the company should havea preventive maintenance schedule in accordance with the conditions of machines on the productionfloor to reduce machine downtime by using modularity design method approach to reducemaintenance costs. Level of maintenance reliability measured using Overall Equipment Effectiveness(OEE), whereas treatment schedule used to obtain parameter Mean Time to Failure (MTTF) andMean Time to Repair (MTTR). Maintenance cost calculator is then performed with correctivemaintenance, preventive maintenance and preventive maintenance with design modularity. By usingmodularity design companies can combine several components into a module to do the replacementcomponents simultaneously causing maintenance costs to be as much as 29.1% less than the companydoing the corrective maintenance activities.